Neonatal Myocarditis: A Review (Dhaka Shishu (Children) Hospital Journal, 2021)
Neonatal myocarditis is a rare and life-threatening disease with clinical symptoms suggesting bacterial sepsis, accompanied by congestive heart failure, cardiogenic shock and arrhythmias. Enteroviruses and adenoviruses are the most frequent pathogens isolated in myocarditis in neonate. Due to extensive myocyte necrosis in the left ventricle, symptoms may mimic myocardial infarction and circulatory collapse. The diagnosis is suggested by an ischaemic electrocardiogram, raised cardiac enzymes and left ventricular dysfunction. These infants are best managed by early recognition of heart failure, avoidance of hypotension and transfer to an ECMO center. No specific antiviral treatment exists for neonatal myocarditis. Even in the presence of sufficient respiratory and circulatory support, the mortality among neonates with viral myocarditis is high. Majority of survivors develop serious cardiac sequelae. Since neonatal myocarditis is a devastating disease and is not often in the differential diagnosis of neonatal collapse, clinicians should keep a high index of suspicion.DS (Child) H J 2019; 35(1) : 70-73